PENGARUH CUSTOMER EXPERIENCE DAN KEPUASAN PELANGGAN PELANGGAN TERHADAP LOYALITAS PELANGGAN SMARTFREN - Mega Hernawan; Cundo Harimurti (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to determine the effect of customer experience and customer satisfaction on customer loyalty to Smartfren. The theory used in this study refers to the opinion of Sheth (Harumi, 2016: 118), which states that, "Customer loyalty is a customer's commitment to a brand, store or supplier, based on a very positive attitude and is reflected in consistent repeat purchases. Loyal customers are individuals who make repeat purchases from the same company, telling other potential customers through word of mouth.” This research was conducted using quantitative methods through the distribution of questionnaires. The population was 60,000 members of Smartfren Community with a sample of 140 respondents. The results of the F-test conducted using SPSS version 26.0 show that Customer Experience and Customer Satisfaction variables simultaneously have a positive and significant influence on Customer Satisfaction. This is evidenced by the fcount value of 78.202, which is greater than the ftable value of 3.06. The positive and significant effect is also evidenced by the value of the determinant of the coefficient of 53.3%.